Maximal forces for peak height and flight distance on vault in mens artistic gymnastics? - Lehmann, T.; Knoll, K.; Naundorf, F.; Seemann-Sinn, A. (Science of Gymnastics Journal, 2024)
Analysing the take-off forces on the vaulting table can help to inform the athlete about the vaulting technique. A measuring device was used to measure the forces during the Artistic World Championships 2019. The greatest forces were measured during Forward handspring. The mean maximum values were 5.4 times body weight (BW). The highest peak height was calculated for Forward handspring (tucked) at 2.9 m. The longest flight distance was 3.62 m for forward handspring and 3.59 m for tsukahara/kasamatsu. The statistical correlations between the forces and the peak height and flight distance could only be verified for Forward handspring. For the Tsukahara/Kasamatsu and the Yurchenko vaults, no correlation could be proven.